1991
DOI: 10.5144/0256-4947.1991.19
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Rotaviral Gastroenteritis at a Referral Centre in Saudi Arabia

Abstract: The incidence of gastroenteritis caused by rotavirus was investigated at a referral hospital in Saudi Arabia over a period of 4.5 years. Of the 1,729 patients with suspected infection, 547 (31.6%) were positive for rotavirus infection. Most were inpatients (65) and 75.7% of the patients were under 12 years of age. Of the 414 positive patients under 12 years of age, 63% were inpatients. Similarly, 74.4% of the 25-year and older group were inpatients. However, 40.3% of them were abnormal hosts because they eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…For example, al-Bwardy et al [1988] reported rotavirus as a major cause of gastroenteritis in children in Riyadh with a prevalence of 44.3%. While Al-Ahdal et al [1991] reported 31.6%. In general the prevalence of rotavirus-positive stools from children with diarrhea ranges from 30% to 50% [Staat et al, 2002].…”
Section: Discussionmentioning
confidence: 94%
“…For example, al-Bwardy et al [1988] reported rotavirus as a major cause of gastroenteritis in children in Riyadh with a prevalence of 44.3%. While Al-Ahdal et al [1991] reported 31.6%. In general the prevalence of rotavirus-positive stools from children with diarrhea ranges from 30% to 50% [Staat et al, 2002].…”
Section: Discussionmentioning
confidence: 94%
“…32 Finally, another article studied the viral contamination of environmental surfaces on general paediatric wards and playrooms in major referral centres in Riyadh. 25 In all, these studies were from six different cities in the Kingdom of Saudi Arabia, namely Jeddah, 20 , 22 , 28 , 30 , 37 , 51 Taif, 21 , 28 Riyadh, 23 , 31 – 35 , 42 Jizan, 24 Dammam, 26 – 27 , 36 and Makkah. 29 These studies were conducted in hospitals ( Table 1 ) in the four major regions of Saudi Arabia ( Table 2 , Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1 , study duration was highly variable, ranging from a few weeks 26 , 27 to several years. 23 Two studies lasted less than a month, and eight others lasted a year or longer. The median study duration was 12.0 months.…”
Section: Resultsmentioning
confidence: 99%
“… Circulation of rotavirus within the country between 1988 to 2008 . RV reported in a high prevalence of diarrhoea cases overall in KSA during 1988 to 2001 [ 6 , 7 , 11 , 12 ]. Recent studies (after 2001) suggest that the incidence may be falling [ 8 , 10 , 13 ].The decrease in the incidence of rotavirus explained by improvements in public health introduced in recent years.…”
Section: Discussionmentioning
confidence: 99%